2003
DOI: 10.1186/1476-069x-2-2
|View full text |Cite
|
Sign up to set email alerts
|

Decreased sex ratio following maternal exposure to polychlorinated biphenyls from contaminated Great Lakes sport-caught fish: a retrospective cohort study.

Abstract: Background: Fish from the Great Lakes are contaminated with polychlorinated biphenyls, which have been found to have several adverse reproductive effects. Several environmental contaminants have been found to alter the sex ratio of offspring at birth, but the evidence of such an effect of polychlorinated biphenyls has been inconsistent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
1
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(62 citation statements)
references
References 55 publications
1
59
1
1
Order By: Relevance
“…Equivocal results exist in relation to parental serum polychlorinated biphenyl (PCB) concentrations among angler populations. A reduced sex ratio (fewer males) was observed among mothers in the highest PCB quintile compared with the lowest quintile, although no relation was observed for paternal exposure, suggesting a maternally mediated effect (Weisskopf et al, 2003). Conversely, a higher sex ratio or male excess was observed in the offspring of a sample of Michigan anglers and their spouses for paternal but not maternal PCB exposure (Karmaus et al, 2002).…”
Section: Mortalitymentioning
confidence: 85%
“…Equivocal results exist in relation to parental serum polychlorinated biphenyl (PCB) concentrations among angler populations. A reduced sex ratio (fewer males) was observed among mothers in the highest PCB quintile compared with the lowest quintile, although no relation was observed for paternal exposure, suggesting a maternally mediated effect (Weisskopf et al, 2003). Conversely, a higher sex ratio or male excess was observed in the offspring of a sample of Michigan anglers and their spouses for paternal but not maternal PCB exposure (Karmaus et al, 2002).…”
Section: Mortalitymentioning
confidence: 85%
“…Accordingly, a recent review concluded that there is no convincing evidence of an association between ΣPCB and secondary sex ratio [44], although some of the studies included in the review did report a significantly decreased sex ratio at increased PCB exposure [5,6]. …”
Section: Discussionmentioning
confidence: 99%
“…Potential confounders were identified using a Directed Acyclic Graph (DAG, Figure 1), based on known associations with sex ratio [3234], methylmercury [29] and POPs [6,35]. Associations between exposures (ΣPCB and p,p’ -DDE) and the secondary sex ratio were tested one exposure at a time in marginal and confounder adjusted logistic regression models.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations